Pengaruh Manfaat dari Kualitas Fitur E-Wallet Terhadap Gaya Hidup Mahasiswa Muslim Solo Raya - Pramesti, Lanjar Dian; Ayuningtyas Putri, Rizky Nur (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
In the development of the current digital era, many transactions are carried out digitally or called an electronic wallet, a digital wallet that facilitates the payment process. The purpose of this study was to determine the effect of the benefits of e-wallet quality on student lifestyles. In this study using quantitative methods with respondent sampling techniques using purposive sampling, namely a sample technique with regard to certain criteria. Respondent data collection was carried out by distributing questionnaires via google form. The number of samples used in this study were 107 respondents. Tests were carried out using SPSS by testing validity, reliability, normality, simultaneous test (F test), partial test (T test), and multiple linear regression to determine the hypothesis of each variable. The test results show that the quality of reliability and empathy influences the utilization of e-wallet features for collage student lifestyles.